2017
DOI: 10.18632/oncotarget.22315
|View full text |Cite
|
Sign up to set email alerts
|

Silencing RIF1 decreases cell growth, migration and increases cisplatin sensitivity of human cervical cancer cells

Abstract: Replication timing regulatory factor 1 (RIF1) plays an important role in DNA replication regulation, stem cell pluripotency and DNA repair pathway. However, little is known about the molecular mechanisms and physiological significance of RIF1 in cancer and chemotherapy efficacy. In this study, we found that RIF1 is upregulated in cervical cancer tissues compared with normal tissues both at mRNA and protein levels through online databases. RIF1 knockdown reduced cervical cancer cell growth, colony formation, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Furthermore, knockdown of RIF1 inhibited DSB repair capacity and cell survival upon cisplatin treatment. These results were consistent with our previous findings in cervical cancer cells 21 .…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, knockdown of RIF1 inhibited DSB repair capacity and cell survival upon cisplatin treatment. These results were consistent with our previous findings in cervical cancer cells 21 .…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, our previous study [52] found that silencing RIF1 increased cisplatin-induced apoptosis in human cervical cancer cells. Hence, it is possible that RIF1 knockdown potentiated ovarian cancer cells to platinum-based cancer treatment by disrupting the NER activity followed by increasing the apoptosis event.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, RIF1 is also involved in embryonic stem cells (ESCs) self-renewal and is highly expressed in mouse ESCs 20 22 . In addition, RIF1 has been reported overexpressed in breast cancer tissues and we previously found that RIF1 knockdown could decrease cell growth and increase cisplatin sensitivity of cervical and ovarian cancer cells 23 25 . Despite the roles listed above, the specific role of RIF1 in NSCLC remains little known.…”
Section: Introductionmentioning
confidence: 87%